ANALISIS PENGARUH INTELLECTUAL CAPITAL TERHADAP ISLAMIC FINANCIAL PERFORMANCE INDEX BANK SYARIAH - Pramitasari, Windy; Wahidahwati, Wahidahwati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to find out the influence of intellectual capital to the financial performance of Syariah Bank in Indonesia. The dependent variable is carried out by using financial performanceof Syariah Bank based on the Islamic Financial Performance Index. The independent variable is carried out by using intellectual capital ismeasured by using Pulicmodel which is VAIC (Value Added Intellectual Coefficient). The sample of this research is Syariah Bank i.e. Bank Umum Syariah (BUS) which is listed in Indonesia Bank in 2010-2014. The sample has been selected by using purposive sampling method and it obtains 10 unit banks and 5 years of observations thenbecomes 50 research samples. The Pulic model of VAIC (Value Added Intellectual Coefficient â VAIC) is used as the efficiency size on the component of intellectual capital; physical capital coefficient (VACA), human capital coefficient (VAHU), and structural capital coefficient (STVA). The analysis research has been done by using partial least square. The result of this research shows that intellectual capital has significant influence to the Islamic financial performance index and it is able to predict the Islamic Financial Performance Index in the future. Besides, the average of intellectual capital (ROGIC) growth also has significant influence to the Islamic financial performance index in the future.Keywords: Intellectual Capital, VAIC, Syariah Accounting, Performance of Syariah Bank